The effect of misoprostol on intraoperative blood loss after myomectomy - Vahdat, Mansoureh; Kashanian, Maryam; Asadollah, Sara; Yazdkhasti, Payman; Nikravan, Nasrin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Uterine myomas are common benign tumors in the reproductive period. Bleeding during myomectomy is one of the major complications. We designed a randomized clinical trial to investigate the effectiveness of misoprostol on reducing Intraoperative Blood Loss (IBL) after myomectomy. Methods: Sixty four patients undergoing abdominal myomectomy were randomized into misoprostol group (n=32) that were given 200 micrograms sublingual misoprostol 0.5 hour before the operation and control group (n=32) that were given placebo. Hemoglobin (Hb) was recorded preoperative, 6 h and 24 h after surgery. Data were analyzed by SPSS software (V.20). Results: Mean of age, body mass index and baseline Hb were not statistically significant between the groups however Hb in 6h after operation were significantly higher in misoprostol group but not significant after 24 h (Hb 6h: 9.8 ±0.8 vs. 9.1 ± 0.9, P=0.003 and Hb 24 h: 10.50 ± 0.56 vs. 10.24 ± 0.58, P=0.066). No difference was observed in terms of anemia and need for blood transfusion after operation among the groups. Conclusions: Preoperative use of sublingual misoprostol is effective in reducing IBL for women undergoing myomectomies in short time (after 6 h). Further studies should be performed to investigate the effectiveness of preoperative misoprostol with various routes and doses in other post-operative time on reducing IBL in abdominal myomectomy.